The "Great Combat C" - Bykanova-Yudanov, n. (Coaching and Sport Science Review, 2017)
Modern technology presents lots of useful statistics about a tennis match. It helps us to dig deeper into its "fabric", to understand tactical patterns, to detect underlying currents and simply follow the match flow being a better equipped spectator. We know where Nadal likes to go with his forehand, we know what serve Federer prefers to use on grass, we can foresee shot selection of Serena Williams from the mid-court and we can detect the preferable height of the ball for Kristina Mladenovic. Match statistics cover practically every bit of technical and tactical mastery of the contenders. Much could be understood about their current physical form. However, the psychological bit remains elusive. This article offers a new look at the tennis match through the introduction of a psychological measurement - the "Combat C" or "Combat Coefficient" - an easy and straightforward measure of contenders` competitive effort.